Fruit productivity and quality in yellow passion fruit orchards with different trellis systems and planting density in the Colombian low tropics - Cleves-Leguízamo, José Alejandro (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2024)
In the last two decades, the cultivation of passion fruit has gained significant importance, as evidenced by the sustained increase in planting area, productivity growth, technological advancements, and the creation of numerous jobs. The trellising system, also known as the support system, is closely linked to the productivity and quality of the fruit, information that is not available for the Colombian Orinoquia. In the municipalities of Granada and Lejanias, yellow passion fruit (Passiflora edulis f. flavicarpa Deg.) orchards with different trellising systems were identified: simple trellis (ES), T or horizontal trellis (T), and total trellis or barbecue (ET). Based on the Colombian technical standard (NTC 1279), weekly records of production volume were taken once production began, considering the quality grades: first, second, and industrial. The variables analyzed were: planting distance, planting density (plants/ha), production cycle duration (months), productivity (kg ha-1), and fruit quality (%). It was found that the simple trellis system (ES) presented significant comparative advantages, such as higher productivity (30.5 t ha-1) with 73% first-quality fruit, followed by the T or horizontal trellis system with 22.8 t ha-1 and 55% first-quality fruit, and finally the total trellis system (ET) with 19 t ha-1 and 39.7% first-quality fruit. Regarding the duration of the crop cycle, no significant differences were found. It was confirmed that the simple trellis system offers the greatest and best competitive advantages, allowing for higher planting density, increased crop ventilation, reduced self-shading, higher photosynthetic efficiency, lower incidence and severity of pests and diseases, and facilitating practices such as mechanization, assisted pollination, pruning, higher efficiency of phytosanitary controls, and lower requirement for synthetic chemical inputs.